Asymmetric centrosome behavior and the mechanisms of stem cell division. - Yamashita, Y.M.; Fuller, M.T. (Journal of Cell Biology, 2008)
The ability of dividing cells to produce daughters with different fates is an important developmental mechanism conserved from bacteria to fungi, plants, and metazoan animals. Asymmetric outcomes of a cell division can be specified by two general mechanisms: asymmetric segregation of intrinsic fate determinants or asymmetric placement of daughter cells into microenvironments that provide extrinsic signals that direct cells to different states. For both, spindle orientation must be coordinated with the localization of intrinsic determinants or source of extrinsic signals to achieve the proper asymmetric outcome. Recent work on spindle orientation in Drosophila melanogaster male germline stem cells and neuroblasts has brought into sharp focus the key role of differential centrosome behavior in developmentally programmed asymmetric division (for reviews see Cabernard, C., and C.Q. Doe. 2007. Curr. Biol. 17:R465-R467; Gonzalez, C. 2007. Nat. Rev. Genet. 8:462-472). These findings provide new insights and suggest intriguing new models for how cells coordinate spindle orientation with their cellular microenvironment to regulate and direct cell fate decisions within tissues.